The GRA17 Parasitophorous Vacuole Membrane Permeability Pore Contributes to Bradyzoite Viability - Paredes-Santos, Tatiana; Wang, Yifan; Waldman, Benjamin; Lourido, Sebastian; Saeij, Jeroen P. (Frontiers in Cellular and Infection Microbiology, 2019)
The Toxoplasma gondii parasitophorous vacuole membrane (PVM) offers protection from the host immune system but is also a barrier for uptake of nutrients from the host. Previously, we showed that GRA17 mediates the tachyzoite PVM permeability to small molecules. During the conversion from tachyzoites to encysted bradyzoites, the PVM remains as the cyst membrane becoming the outer layer of the cyst wall. Little is known about how small molecules, such as nutrients, enter cysts. To characterize GRA17’s role in cysts, we deleted GRA17 in the type II ME49 cyst-forming strain. ME49gra17 parasites have reduced growth and formed grossly enlarged “bubble vacuoles”, which have reduced PVM small molecule permeability. ME49gra17 parasites formed cysts in vitro at rates comparable to the wild-type, but the viability of the bradyzoites inside these cysts was significantly reduced compared to wild-type bradyzoites. Genetic complementation of ME49gra17 with GRA17 expressed from the endogenous or tachyzoite-specific SAG1 promoter recovered the viability of bradyzoites. Complementation with the bradyzoite-specific SRS9 promoter drastically increased the viability of bradyzoites, demonstrating the importance of GRA17 in regulating bradyzoite viability inside cysts. Mice infected with a high dose of ME49gra17 parasites did not contain parasites in their brain nor did mice infected with ME49gra17 complemented with GRA17 expressed from a bradyzoite-specific promoter. Our results suggest that the ME49Δgra17 strain is avirulent and is cleared before it can reach the brain and that GRA17 not only plays an important role during acute infections but is also needed for viability of bradyzoites inside cysts.